Risk of ovarian cancer in women with symptoms in primary care: population based case-control study. (25th August 2009) - Hamilton, William; Peters, Tim J; Bankhead, Clare; Sharp, Deborah
Abstract : Objective To identify and quantify symptoms of ovarian cancer in women in primary care. Design Case-control study, with coding of participants' primary care records for one year before diagnosis. Setting 39 general practices in Devon, England. Participants 212 women aged over 40 with a diagnosis of primary ovarian cancer, 2000-7; 1060 controls matched by age and general practice. Main outcome measures Odds ratios and positive predictive values for symptoms from conditional logistic regression analyses. Results Seven symptoms were associated with ovarian cancer in multivariable analysis. The univariable positive predictive values and multivariable odds ratios (with 95% confidence intervals) for these were 2.5% (1.2% to 5.9%) and 240 (46 to 1200) for abdominal distension; 0.5% (0.2% to 0.9%) and 24 (9.3 to 64) for postmenopausal bleeding; 0.6% (0.3% to 1.0%) and 17 (6.1 to 50) for loss of appetite; 0.2% (0.1% to 0.3%) and 16 (5.6 to 48) for increased urinary frequency; 0.3% (0.2% to 0.3%) and 12 (6.1 to 22) for abdominal pain; 0.2% (0.1% to 0.4%) and 7.6 (2.5 to 23) for rectal bleeding; and 0.3% (0.2% to 0.6%) and 5.3 (1.8 to 16) for abdominal bloating. In 181 (85%) cases and 164 (15%) controls at least one of these seven symptoms was reported to primary care before diagnosis. After exclusion of symptoms reported in the 180 days before diagnosis, abdominal distension, urinary frequency, and abdominal pain remained independently associated with a diagnosis of ovarian cancer. Conclusions Women with ovarian cancer usually have symptoms and report them to primary care, sometimes months before diagnosis. This study provides an evidence base for selection of patients for investigation, both for clinicians and for developers of guidelines.